Differential Expression Analysis of Olfactory Genes Based on a Combination of Sequencing Platforms and Behavioral Investigations in Aphidius gifuensis - Fan, Jia; Zhang, Qian; Xu, Qingxuan; Xue, Wenxin; Han, Zongli; Sun, Jingrui; Chen, Julian (Frontiers in Physiology, 2018)
Aphidius gifuensis Ashmead is a dominant endoparasitoid of aphids, such as Myzus. persicae and Sitobion avenae, and plays an important role in the controlling of aphids in various habitats, including tobacco plants as well asand wheat in China. The use of A. gifuensis has been successfully applied for the biological control of aphids, especially M. persicae, has been successfully applied in green houses and fields in China. The corresponding parasites, as well as its mate- searching behaviors are subjects of considerable interest. Previous investigations of the A. gifuensis transcriptome studies have relied on short-read next-generation sequencing (NGS) technology, and the vast majority of the resulting isotigs do not represent full-length cDNA sequences. Here, we employed a combination of NGS and single- molecule real-time (SMRT) sequencing of virgin females (VFs), mated females (MFs), virgin males (VMs) and mated males (MMs) to provide a complete view ofcomprehensively study the A. gifuensis transcriptome. Investigations of the bBehavioral responses to the aphid alarm pheromone (E-β-farnesene, EBF) as well as to A. gifuensis of the opposite sex were also conductedstudied. The results showed that: 1. The VMs were found to be attracted by female wasps, and; the MFs were repelled by male wasps; however,whereas the MMs and VFs did not respond to the opposite sex. of wasps. 2. In addition, The VFs, MFs and MMs were attracted by EBF,; while, VMs did not respond. According to these results, we performed a personalized differential gene differential expression analysis of olfactory gene sets (66 odorant receptors, 25 inotropic receptors, 16 odorant-binding proteins and 12 chemosensory proteinsORs, 25 IRs, 16 OBPs as well asand 12 CSPs) in virgin and mated A. gifuensis of both sexes were analyzed, and identified 13 candidate genes were screened out; andand the trends for these genes were found to be whose expression levels were highly consistent with the potential trends in the behavioral test results, suggesting potential functions for these genes in pheromones perception.